Optimalisasi Perilaku Hidup Bersih Dan Sehat (Phbs) Masyarakat Melalui Edukasi Pola Konsumsi - Fadhil, Muhammad Luthfi Irsyadul; Al Kahfi, Muhammad; Zandy, Rozan Kusuma; Fathurrahman, Farhan; Susilo, Muhammad Wangsa Putranto; Afrilia, Ananda; Nafasari, , Dyah Linda Syafina; Sulistyowati, Yuyun; Razani, Athaya Fairuz Damalika; Khasanah, Oktavia Putri; Nurdianto, Talqis (Universitas Muhammadiyah Yogyakarta, 2025)
The application of a healthy and clean lifestyle in daily life can determine the sustainability of a community’s well-being. A clean and healthy lifestyle can begin with the cleanliness and health of the household kitchen in each family. However, many people still do not pay attention to this lifestyle. For example, some people in Sarwodadi, Pejawaran, Banjarnegara, still neglect the cleanliness and health of their household kitchens. The kitchen is a place for preparing and serving food to the family. The cleanliness and health of the kitchen and food processing directly affect the family members' health. This community service program aims to raise awareness and understanding among PKK (Family Welfare Program) mothers regarding Clean and Healthy Living Behavior (PHBS) through education on healthy consumption patterns of side dishes to improve family health quality. The methods used include interactive counseling, distribution of educational posters, and a follow-up program called